FEATURES OF DISTRIBUTION OF HEAVY METALS IN FISHES FAMILY GOBIES (GOBIIDAE) WITHIN BUG ESTUARY - Cмирнова С.М.; Васильєва, Т.А.; Смирнов, В.М. (World of Medicine and Biology, 2016)
The content of heavy metals was analyzed in fishes family Gobies of Bug estuary. Found that in the head of fish mainly concentrates Cr (almost 100%), fins accumulate Pb (34%), Zn, Ni (28%), squama - Ni (37%), Fe, Cu (30%), Mn (28 %),offal - Fe (26%), Cu, Pb (23%), bone - Zn (22%). Soft tissues are not accumulate heavy metals.